Forecasting denosumab - Calkins, Tim (SAGE knowledge. Cases., 2016)
This case looks at an important business task: forecasting a new product. The case can be used to teach finance, marketing (new product introduction), and healthcare strategy. The product is one of Amgen's most important new products: denosumab. On the surface, the case is fairly easy; students simply have to do some simple mathematical calculations. However, the challenges of forecasting quickly become apparent; every forecast depends on some critical assumptions, and the answer can vary dramatically.